2001
DOI: 10.1002/mop.10029
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of three‐dimensional MMIC by spectral–pseudospectral domain technique

Abstract: In this paper, a spectral–pseudospectral domain technique is presented for the full‐wave analysis of a three‐dimensional MMIC. This technique combines the advantages of pseudospectral method of lines with those of spectral‐domain analysis. In conjunction with the cavity‐resonance technique, it enables one to efficiently extract the s‐parameters of three‐dimensional planar circuits. To demonstrate the generality and validity of the proposed method, numerical analyses are performed for several structures such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…It has also been shown that polarization-insensitive optical gain over a wide bandwidth can be realized in a coupled quantum wells [7]. Recently, a new method of achieving polarization insensitivity in MQW modulators was analysed [8], based on introducing a thin layer inside quantum well. An application of this idea to SOA has been published in [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been shown that polarization-insensitive optical gain over a wide bandwidth can be realized in a coupled quantum wells [7]. Recently, a new method of achieving polarization insensitivity in MQW modulators was analysed [8], based on introducing a thin layer inside quantum well. An application of this idea to SOA has been published in [9].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the computational burden, including CPU time and memory storage requirements, is considerably reduced in comparison with classical finite difference (FD) schemes. Therefore, this semi-analytical procedure saves a lot of computing time and thus finds a wide application [1][2][3][4][5][6][7][8]. However, this method increases the solution accuracy by removing the mesh dependence in the mesh line direction, the discrete error still exists in the other directions.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the aim is to convert the partial differential equations into analytically solvable ordinary differential equations with minimal discretization. Conventionally, one of the partial derivatives is replaced by a finite difference, and this technique has been successfully applied in simulating and modeling multilayer planar circuits [5], [6]. To expand the scope of analysis, the method of finite elements has been employed to carry out the discretization process [7]- [10].…”
Section: Introductionmentioning
confidence: 99%
“…To break through this barrier in the modern precious and fast analysis, a lot of high-order discretization methods of the Helmholtz equation have been developed [9]. Recently, pseudospectral disctretization [14], famous for its high accuracy and high convergence rate, has been introduced into MoL in the non-hybrid mode of the hollow metallic waveguide [15] and hybrid mode of the planar microstrip structure [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the solution accuracy for pseudospectral-based method of lines is highly improved [15][16][17]. Because only one dimension needs discretization for two-dimensional boundary values, the difficulties for pseudospectral method to treat irregular domain can also be partly avoided if it is combined with method of lines.…”
Section: Introductionmentioning
confidence: 99%